Андрій Головко в контексті українського соцреалізму - Хархун, В. (Літературознавчі обрії. Праці молодих учених, 2010)
Andriy Holovko’s role of Ukrainian socialist realism «initiator» is analyzed in the article. The paper discusses a post-Soviet reconstruction of Andriy Holovko’s biography and literary works. Particular attention is paid to the «literary struggle» between Andriy Holovko and Hnat Mykhaylychenko for the creation of revolution myth to achieve the leading place in the socialist realist canon.